AN ELECTROPHORETIC STUDY ON SERUM PROTEINS IN NORMAL ARABIAN RACE HORSES - Sultan , A Sh; AL-Delaimi , A.K.A (The Iraqi Journal of Veterinary Medicine, 2022)
Electrophoretic Pattern of Serum proteins were studied in thirty normal Arabian race horses. The resolution of the serum protein fractions in 24 (80%) of horses, group I revealed five fractions, albumin and the globulins (a1, a2, B and y). The total serum protein was ranged from ( 6.2-8.4 gm/dL) with mean (7.57 ±0.17) in the this group of horses. Where-as four fractions, albumin and the globulins (a2, B and y) were observed in 6(20%) of horses, group 2. The total serum protein was ranged from (6.0 - 7.4 gm/dL) with mean (6.76 ± 0.27) in that group of horses. The Albumin/Globulin ratio in both Groups was (0.66 ±0.13); (0.89 ± 0.07), respectively.